Access to hip and knee replacement surgery in patients with chronic diseases according to patient-reported pain and functional status - Bélène Podmore; Andrew Hutchings; Sujith Konan; John Robson; Jan van der Meulen (BMC, 2020)
Abstract Background An increasing number of patients undergoing hip or knee replacement have chronic diseases. It has been suggested that the presence of chronic diseases may affect access to this type of surgery in the English National Health Service (NHS). We examined the access to hip and knee replacement surgery in patients with and without chronic diseases according to preoperative patient-reported pain, functional status and symptom duration. Methods We analysed data of 640,832 patients who had hip or knee surgery between 2009 and 2016 in England. Multivariable regression was used to estimate the impact of 11 chronic diseases on severity of joint problems as measured on a scale from 0 to 48 by Oxford Hip (OHS) and Knee Scores (OKS) just before surgery and on likelihood of long-standing joint problems (> 5 years pre-operatively). Results Patients with chronic diseases reported more severe joint problems than patients without (OHS differences ranged from 1.1 [95% CI 0.93, 1.2] to 2.5 [95% CI 2.3, 2.7] and OKS differences from 0.5 [95% CI 0.3, 0.7] to 2.6 [95% CI 2.4, 2.7] for the 11 chronic diseases) but the differences remain small. When analysed separately, patients with chronic diseases reported both more severe pain and poorer functional status. Six chronic diseases in hip patients and two in knee patients increased the likelihood that they had long-standing joint problems. The severity of joint problems just before surgery increased with the number of chronic diseases (OHS differences; one chronic disease (1.5 [95% CI 1.4, 1.5]) to four or more (5.8 [95% CI 5.6, 6.0])). Conclusions Patients with chronic diseases reported more severe joint problems immediately before hip or knee replacement surgery suggesting they have hip or knee replacement later in the course of their joint disease.